PERTIMBANGAN HUKUM DITERIMANYA PENGAJUAN PRAPERADILAN PELAKU TINDAK PIDANA KORUPSI PROYEK JALAN DI KABUPATEN LAMPUNG TIMUR - Sonia Citra Lestari, Zainudin Hasan (Universitas Muhammadiyah Metro, 2022)
Pretrial as a guarantee for anyone who is negligence or intentional from the attitude of law enforcement, if law enforcers are negligent in carrying out their duties, the suspect has the right to file a pretrial. This study discusses how the process of investigating criminal acts of corruption, how the procedure for filing a pretrial against perpetrators of criminal acts of corruption, how the judge's consideration in imposing pretrial decisions against perpetrators of criminal acts of corruption. This study uses a normative and empirical juridical approach. Collecting data by field studies and literature studies. Data analysis was carried out in a qualitative juridical manner, namely the analysis was carried out descriptively. This pretrial institution aims to protect the suspect's human rights as regulated in the Criminal Procedure Code.